2015
DOI: 10.1038/ismej.2015.109
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic study of red biofilms from Diamante Lake reveals ancient arsenic bioenergetics in haloarchaea

Abstract: Arsenic metabolism is proposed to be an ancient mechanism in microbial life. Different bacteria and archaea use detoxification processes to grow under high arsenic concentration. Some of them are also able to use arsenic as a bioenergetic substrate in either anaerobic arsenate respiration or chemolithotrophic growth on arsenite. However, among the archaea, bioenergetic arsenic metabolism has only been found in the Crenarchaeota phylum. Here we report the discovery of haloarchaea (Euryarchaeota phylum) biofilms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 39 publications
4
86
0
2
Order By: Relevance
“…The number and diversity of the identified proteins suggest that many microorganisms in this environment are capable of using arsenic as an energy source. This mechanism could be widespread in high altitude Andean arsenic systems, as shown in findings at Diamante Lake 8 .
Figure 6ArrA subfamily maximum likelihood tree. The arsenite oxidases clade ArxA is shown in light grey and the arsenate reductases in dark grey.
…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The number and diversity of the identified proteins suggest that many microorganisms in this environment are capable of using arsenic as an energy source. This mechanism could be widespread in high altitude Andean arsenic systems, as shown in findings at Diamante Lake 8 .
Figure 6ArrA subfamily maximum likelihood tree. The arsenite oxidases clade ArxA is shown in light grey and the arsenate reductases in dark grey.
…”
Section: Resultsmentioning
confidence: 83%
“…These enzymes are frequently present in environments where arsenic is rife. In Archaea, they were reported for the first time at Diamante –another HAAL located in the caldera of Galán Volcano– with an As content in water of 119 mg L −1   8 . The respiratory oxidases and reductases are large proteins, with usually at least 800 residues, so only a limited number was available for phylogenetic trees, as complete genes could only be found in the larger contigs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not unreasonable to expect that they may be present on Mars or other planetary bodies, and current thought is that arsenic may have been important to early life on Earth. It is well known that arsenic and selenium are respired by a number of terrestrial microorganisms to conserve energy (Stolz and Oremland, 1999;Zhu et al, 2014;Nancharaiah and Lens, 2015;Rascovan et al, 2016). Interestingly, this study identified 10 microorganisms that grew in media where arsenic was the only terminal electron acceptor available.…”
Section: Discussionmentioning
confidence: 92%
“…Together with the recent demonstration of the ability of haloarchaea to oxidize CO (King, 2015), to participate in dissimilatory arsenic cycling (Rascovan et al, 2016) and to actively mineralize insoluble polymers such as chitin and cellulose (Sorokin et al, 2015), it significantly shifts our perception of haloarchaea as an important biogeochemical actor in hypersaline habitats.…”
mentioning
confidence: 99%